Miniaturized Minkowski-Island Fractal Microstrip Antenna Fed by Proximity Coupling for Wireless Fidelity Application - I Putu Elba Duta Nugraha; Indra Surjati; Syah Alam (Universitas Ahmad Dahlan, 2017)
This paper proposed a new design of Minkowski Island microstrip antenna fed by proximity coupling with partial ground plane. The design was consisted of two layers of substrate, on the top substrate was the antenna patch and on the bottom substrate was the proximity feed line and the partial ground. At the first stage, the normal square patch antenna was mainly designed. Then, the Minkowski patch antenna was designed using 1st iteration technique and 2nd iteration technique. The Minkowski fractal shape slot was embedded in the center of the patch to form a Minkowski Island patch antenna. Using the Minkowski Island fractal technique, the dimension of the patch can be reduced up to 58.7%. The proximity feed line in this design was used to increase the impedance bandwidth, and from the measurement the impedance bandwidth of the proposed antenna was 240 MHz with return loss of -24.54 dB and VSWR of 1.126.